NEOREALIST ASEAN IN 2020: INDONESIAN PERSPECTIVE - SuryadiSyarif, Moh. SuryadiSyarif; Rahman, Abd.; Francoise, Jeanne (International Journal of Psychosocial Rehabilitation, 2019)
This paper, that would be presented in International Academic Conference on Research in Social Sciences (IACRSS), Oxford, UK, 8-10 November 2019, has a preliminary analysis that ASEAN would strengthen up defense cooperation starting in the year of 2020, because ASEAN had discussed about “non-interference” policy security dilemma, despite of potential conflict in South China SEA, and political power binding in United Nations, regarding issues of Terrorism and Global Warming. This paper is using the concept of Indonesian National Defense System (SistemPertahanan Negara Republik Indonesia/ Sishanneg) because all the analysis is coming from Indonesian perspective; how Indonesian think about ASEAN defense system, what kind of profit would Indonesian get after the unity of the defense, and what Indonesia could contribute in that kind of defense. The second theory used in this paper is Neorealism, because each country must have their own analysis and capacity, yet including national budget, to protect their citizens. This is why the unity of defense is different with economic cooperation, because it is needed a real focus and real purpose to unify the defense, but it just took only bargaining process in economic cooperation while each country does not need to have common grounds with other country. This paper has purpose to be seen as academic recommendation for Indonesian Ministry of Defense and Indonesian Ministry of Foreign Affairs to analyze again about ASEAN opportunity to be united in deeper way, than just economical approach, but also defense